Encontros e desencontros nas vozes de crianças na escola do campo da Comunidade Vila Jordão, Bonito-PA - CORDEIRO, Silvio José Travassos (2024)
This academic work on educational processes in rural schools is the result of studies and dialogues promoted by the Center for Studies and Research on Childhood, Education and Culture in the Para Amazon, associated with the Research Project - The social grammars of children and their childhoods in water territories in regions of the Para Amazon - CNPq/MCTI/FNDCT, which aroused the interest of its members in listening to what children say about the school where they study and what their senses and meanings are. The central objective is to identify and analyze the meanings and significance attributed to the school by the children about the educational activity of the rural school, Vila Jordão Community, Bonito municipality, Pará state, and its relationship with school performance. Methodologically, this is a qualitative approach with field research carried out between March 3 and 11, 2022. The research participants are children aged between 7 and 10. In order to listen to the subjects, we used different approaches that complement each other: bibliographical research, drawings, observations and listening to the students and their families living in the area. We anchored the study in theoretical references from the field of education, childhood and rural education and the following authors: Caldart (2004), Freitas (2005); Ferreira and Nunes (2014), Evangelista and Marchi (2022), among others. The research showed that the children want a school that offers meaningful learning with elements of their play culture, respecting their traditions and the time they have to be children. It is also important that the rural school is a fundamental space-time for human formation, existence and peasant resistance.